A coupled-line balun for ultra-wideband single-balanced diode mixer - M. Y. Algumaei; N. A. Shairi; Z. Zakaria; A. M. Zobilah; N. Edward (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A multi-section coupled-line balun design for an ultra-wideband diode mixer is presented in this paper. The multi-section coupled-line balun was used to interface with the diode mixer in which it can deliver a good impedance matching between the diode mixer and input/output ports. The mixer design operates with a Local Oscillator (LO) power level of 10 dBm, Radio Frequency (RF) power level of -20 dBm and Intermediate Frequency (IF) of 100 MHz with the balun characteristic of 180° phase shift over UWB frequency (3.1 to 10.6 GHz), the mixer design demonstrated a good conversion loss of -8 to -16 dB over the frequency range from 3.1 to 10.6 GHz. Therefore, the proposed multi-section coupled-line balun for application of UWB mixer showed a good isolation between the mixer’s ports.